The Implementation of the Concept of the Good School or vice versa - Targamadzė, Vilija (Acta Paedagogica Vilnensia, 2019)
The Good School concept was approved back in 2015, yet its implementation is rather problematic. It is not easy to tell exactly why that is the case, but some insights could be found by systematically observing the concept’s manner of proceeding (Lat. modus procedendi) and manner of living (Lat. modus vivendi). The insight method is a new and risky chance to take a look at the implementation of the Good School concept. Moreover, it is also an undoubtedly theoretically and practically significant opportunity for insight into the implementation of the theoretical model, which opens new opportunities for improvements related to said model’s realisation. The analysis of the implementation of the Good School concept within the context of the levels of educational reality has shown that the documents being passed at the societal level of this reality are getting mired at the systemic level, because the documents being prepared by the Ministry of Education, Science and Sport and its subordinate institutions lack harmony with the space of content of the Good School concept. A rift between modus procedendi and modus vivendi manifests – the manner of living cannot form due to the conceptual chaos within the documentation. This is also affected by the particular understanding employed by some people acting within the education system when it comes to Good School and learning outcomes. Thus, discussions are needed to address the understanding of the Good School concept. By analysing the implementation of the Good School concept within the context of the levels of educational reality and from the perspective of modus procedendi and modus vivendi, it can be concluded that: • from a legal standpoint, the modus operandi is purposeful at the societal level of the educational reality, and a significant rift is being observed at the systemic level, because the projects and legally significant documents being prepared by the Ministry of Education Science and Sport and its subordinate institutions often are dissonant with the Good School Concept. This, invariably, has an impact not only on the preparation of the documents, but also the monitoring of the implementation of the Good School concept. Thus, people working within the education system have to not only comprehend the Good School concept, but also be able to follow it while preparing any documentation; • the Good School concept is known at the institutional, interpersonal, and intrapersonal levels of educational reality, aspects of it being in action are being noted, as demonstrated by responses from students, teachers, parents, and school leaders. However, this has essentially no connection to the school’s community – modus vivendi has not yet become a part of ‘self’ for the school or the people that operate within it. Thus, purposeful action is needed in the direction of the implementation of the Good School concept, particularly, emphasizing key aspects of the Good School mission: basing school activity on humanistic values, the significance of successful learning by the pupil, the aspects of their improvement and discoveries, and the significance of community agreements with regards to the school’s activities.